Development of E-Module Science Local Wisdom to Improve Students' Global Diversity Character - Astutik, Puji; Sarwanto*, Sarwanto; Sukarmin, Sukarmin; Daud, Anis Nazihah binti Mat (Universitas Syiah Kuala, 2025)
Technology makes students increasingly distant from the noble culture in their area, and educators are obliged to rebuild students' love for the noble culture of their predecessors. Integrating local wisdom in science learning can provide meaningful experiences for students in finding concepts from the surrounding environment. It can train students to love and be proud of their own culture. This study aims to develop a design for an e-module science local wisdom suitable for use as teaching materials in science subjects. The method used in the study is research and development with a 4D model and is limited to the development stage. Research data were collected using interview techniques with teacher and student respondents; the results of the interviews were used to design an e-module that met the needs. The e-module was then tested for its feasibility through validity and readability tests. Based on the needs analysis, an e-module science local wisdom themed ledre Bojonegoro was designed. This e-module is arranged sequentially using inquiry syntax and is divided into 4 stages of learning, namely let's think, let's experiment, let's learn, and let's test understanding, and each stage is integrated with local wisdom ledre Bojonegoro. The local wisdom science e-module is a digital teaching material product that is suitable for use as a science teaching material to improve students' global diversity character, with an average content validity value of 0.95 and an e-module readability percentage of 90%